Implikasi Corporate Social Responsibility (CSR) Terhadap Kinerja Keuangan Perusahaan Yang Memperoleh Sustainability Reporting Award (SRA) - Yeni Octaviani Zalukhu; Heri Afrilianto Manalu; Munawarah Munawarah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
The Purpose of this study is to test or analyze the financial of the use of corporate social responsibility. The measurement of social responsibility is based on general reporting initiative or often reffered to as GRI used in testing. Explanatory research with a quantitative approach aims to analyze a theory that is used to determine whether an hypothesis is accepted or rejected by a previous trial. Companies that have joined the winner of Sustainability Reporting Awards (SRA) have a total of 32 companies as a sample population for testing observations that publish their sustainability review activities clearly and were listed on the Indonesia stock Exchange in the 2015-2018 period. Purposive sampling where the are 19 companies outlined in the test so that the sample used for 4 years to 76 samples as a means of observation test. Descriptive analysis and inferential analysis are 2 ways to analyze the research data test. Comparison of data translation methods using the classic assumption test and hypothesis testing. The conclusion from this study is expected to be able to have the accuracy of research data if corporate social responsibility (CSR) does not significantly influence return On Assets (ROA), Corporate Social Responsibility (CSR) does not significantly influence Return On Equity (ROE), Corporate Social Responsibility (CSR) does not significantly influence the Price Book Value (PBV).